Suya Taco and Sol de Mayo mafic complexes from eastern Sierras Pampeanas, Argentina: Evidence for the emplacement of primitive OIB-like magmas into deep crustal levels at a late stage of the Pampean orogeny - Tibaldi, Alina María (2008)
The age and petrogenetic features of the Suya Taco and Sol de Mayo mafic complexes reported here provide important new insights into the tectonic setting and evolution of the Pampean orogen. Specifically, the results of this study support models that are capable of explaining the introduction of non-arc mantle-derived mafic magmas into the developing orogen at or very near the time of its metamorphic peak. Although a continental collision model for the Pampean orogen cannot be categorically ruled out, an additional slab break-off or lower crustal delamination event immediately following collision would be required in order to account for the observations presented here. Alternatively, the recently proposed hypothesis of subduction of a mid-ocean ridge beneath an accretionary prism as the cause for Pampean orogeny can account for rise of non-arc, OIB-like mafic magmas through an already thickened supracrustalassemblage, as well as the close spatial and temporal association of this magmatism with the development of high-grade granulitic metamorphic and migmatitic assemblages in the Pampean supracrustal rocks.